1987
DOI: 10.1177/002199838702101205
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology for Accurate Shear Characterization of Unidirectional Composites

Abstract: A combined experimental-analytical methodology is presented for accurate determina tion of the intralaminar shear modulus G 12 of unidirectional composites using the off-axis tension test and/or the Iosipescu test. It is demonstrated that consistent values of G 12 can be obtained with the two methods provided that: (1) specimen geometry is optimized for the off-axis test, (2) correction factors are employed to account for the shear stress nonuni formity in the test section of Iosipescu specimens. The problem o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…Xavier et al [32] carried out FEM analysis in order to determine the stress field in the test section of Iosipescu and off-axis tensile tests for the characterization of wood. Regarding off-axis tensile test, they found that by using oblique tabs a uniaxial and uniform stress state is obtained throughout the test section and that no correction factors are needed, which is contrary to the statements of several authors [21,23,24].…”
Section: In-plane Shear Strengthmentioning
confidence: 69%
“…Xavier et al [32] carried out FEM analysis in order to determine the stress field in the test section of Iosipescu and off-axis tensile tests for the characterization of wood. Regarding off-axis tensile test, they found that by using oblique tabs a uniaxial and uniform stress state is obtained throughout the test section and that no correction factors are needed, which is contrary to the statements of several authors [21,23,24].…”
Section: In-plane Shear Strengthmentioning
confidence: 69%
“…Unfortunately, no investigations were performed to verify this thesis [3,7,16]. Other authors propose to interpret the shear stress recorded at the appearance of final crack as the shear resistance.…”
Section: Fig 4 Scheme Of Kinetic Load Of the Specimenmentioning
confidence: 93%
“…These tests are quite straightforward to perform and to analyse when measuring the elastic properties. For the in-plane shear modulus (G 12 ) off-axis, ±45° and Iosipescu test coupons are used, but these tests are not so straightforward to analyse since a complex stress/strain state is induced in the coupons; further details on this subject are well documented in the literature [33][34][35][36][37].…”
Section: W O O D H E a D P U B L I S H I N G L I M I T E Dmentioning
confidence: 99%
“…However, the measurement of the in-plane shear modulus requires the use of off-axis specimens. Although consistent values of in-plane shear modulus may be obtained, specimen geometry must be optimized to reduce the errors provoked by the end-constraint effect [34]. …”
Section: W O O D H E a D P U B L I S H I N G L I M I T E Dmentioning
confidence: 99%